Analisis Komponen Yield Minyak Mikro Alga Hijau Dengan Medium Detmer - Bahagia Bahagia; Vera Viena (Fakultas Teknik, 2019)
This study examines CO2 for the growth of green microalgae by cultivating algal strains in a tank type reactor or fermentor. The study included optimization of the productivity of green algae in the capture of CO2 which can be used as a greenhouse gas catcher. Green algae were isolated from several waters in Banda Aceh and Aceh Besar. The microalgae species of this isolation and its identified species were subsequently cultivated in a tank-shaped cultivation (cultivation) container with 4 flourescent lamps (2x8 watts; 4x8 watts) installed on the outside side of the tank. This study evaluated the comparison of the growth of aerated microalgae O2 (1.25 liters / minute) with fixation of CO2 (1 and 2 liters / minute). The capture of CO2 into carbon dioxide is done by looking at the growing biomass, and the yield content of oil in biomass. The results showed that there were significant differences in the growth patterns of microalgae given O2 aeration and CO2 fixation. Modified CHU 13 Detmer Modified media does not provide a significant difference to algal growth. With a large intensity of light with a medium that is sufficient to increase the growth of microalgae until it reaches the death phase. Component analysis by Chromatography Gas Mass Spectrometry (GC-MS) shows that the largest component in vegetable oils from green microalgae is Palmatic acid (9.36%), Thiogeraniol (24.63%), Cyclopropane Methanol (2.45%), Farnesol ( 2.39%), Trimethyl (2.78%) and Dodencadien (5.06%).